2009
DOI: 10.1007/s00335-009-9192-7
|View full text |Cite
|
Sign up to set email alerts
|

Imprint switch mutations at Rasgrf1 support conflict hypothesis of imprinting and define a growth control mechanism upstream of IGF1

Abstract: Rasgrf1 is imprinted and expressed preferentially from the paternal allele in neonatal mouse brain. At weaning, expression becomes biallelic. Using a mouse model, we assayed the effects of perturbing imprinted Rasgrf1 expression in mice with the following imprinted expression patterns: monoallelic paternal (wild type), monoallelic maternal (maternal only), biallelic (both alleles transcribed), and null (neither allele transcribed). All genotypes exhibit biallelic expression around weaning. Consequences of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 45 publications
2
41
1
Order By: Relevance
“…We found that the Rasgrf1 gene was maternally expressed in the liver and small intestine, paternally expressed in the lung, and biallelically expressed in the brain, heart, spleen, kidney, stomach, pancreas, fat, testis, ovary, longissimus dorsi, and pituitary. These observations are not consistent with those from imprinting reports about the mouse and rat Rasgrf1 gene (Plass et al, 1996;Dockery et al, 2009;Drake et al, 2009). The differential imprinting status of the Rasgrf1 gene among rat, mouse and pig may be caused by the different species or the different tissues that were examined.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…We found that the Rasgrf1 gene was maternally expressed in the liver and small intestine, paternally expressed in the lung, and biallelically expressed in the brain, heart, spleen, kidney, stomach, pancreas, fat, testis, ovary, longissimus dorsi, and pituitary. These observations are not consistent with those from imprinting reports about the mouse and rat Rasgrf1 gene (Plass et al, 1996;Dockery et al, 2009;Drake et al, 2009). The differential imprinting status of the Rasgrf1 gene among rat, mouse and pig may be caused by the different species or the different tissues that were examined.…”
Section: Discussioncontrasting
confidence: 92%
“…neonatal brain, heart, stomach, and liver (Plass et al, 1996;Dockery et al, 2009). The imprinting of the mouse Rasgrf1 gene in a few tissues is relaxed during development, the transition from strongly and predominantly paternal allelic expression to biallelic expression can be seen over time, and expression becomes biallelic around the time of weaning (Drake et al, 2009). Interestingly, compared to the imprinted expression of the Rasgrf1 gene in mouse and rat, we observed a variance in the imprinting of the Rasgrf1 gene in domestic pigs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies of the murine RASGRF1 ortholog (Rasgrf1) show that it is predominantly expressed from the paternal allele in neonatal brain tissue, with expression becoming biallelic during weaning and later into adulthood (Plass et al, 1996;Drake et al, 2009). The spatio-temporal expression patterns of this gene have led to suggestions that it may play a role in memory and learning (Giese et al, 2001).…”
Section: Snp Validation In Candidate Bovine Imprinted Genesmentioning
confidence: 99%
“…The spatio-temporal expression patterns of this gene have led to suggestions that it may play a role in memory and learning (Giese et al, 2001). Gene knockout studies have shown that mice strains deficient in Rasgrf1 activity display a moderate reduction in body weight (15% to 30%) compared to wild-type strains, suggesting a role for Rasgrf1 in post-natal growth and development (Giese et al, 2001;Clapcott et al, 2003;Drake et al, 2009). Interestingly, the differential Rasgrf1 gene expression levels in the mice models resulted in concordant differential expression of Igf1 (the insulin-like growth factor 1 gene) and molecular components of the growth hormone/insulin-like growth factor 1 (GH/IGF1) axis, which are essential for normal growth and development (Drake et al, 2009).…”
Section: Snp Validation In Candidate Bovine Imprinted Genesmentioning
confidence: 99%
See 1 more Smart Citation